DOES FEMALE EDUCATION GENERATE ECONOMIC GROWTH? AN EMPIRICAL ANALYSIS OF WESTERN BALKAN COUNTRIES - JUSAJ, Yvesa; FETAI, Besnik (Studia Universitatis Babeș-Bolyai Oeconomica, 2022)
This paper investigates the relationship between female education and economic growth in Western Balkan countries during the period 2000-2019. The motive behind choosing Western Balkan countries was because there is insufficient research that has been made in this field of study; hence, this research assists to expand the issue of this topic. By using GDP as dependent variable, the paper addresses the question whether female education generates or not economic growth. The techniques applied for this study are OLS, fixed and random effects, and Hausman-Taylor model IVs. The findings show a positive relationship between GDP per capita, female labor participation, school enrollment primary, and literacy rate. On the other hand, there exists a negative relationship with fertility rate, while the school enrollment tertiary is statistically insignificant. This paper brings evidence that female education generates more economic growth in Western Balkan countries. Therefore, the Government of the Western Balkans should take into consideration to invest more on education of the woman in those countries. These in turn will lead to higher economic growth. JEL Classification: I24, J16, J21, O1, O57;